2002
DOI: 10.1366/000370202760354803
|View full text |Cite
|
Sign up to set email alerts
|

Pigment Identification by Fiber-Optics Diffuse Reflectance Spectroscopy

Abstract: Fiber-optics reflectance spectroscopy is used to identify pigments in pictorial layers of works of art thanks to a spectra database of dry powdered mineral pigments. Measurements are noninvasive, without any contact, and can be implemented in situ, without moving the work of art under investigation from its conservation place. The experimental device, using the special back-scattering configuration, is briefly presented. The protocol leading to the constitution of the spectra database of dry mineral pigments i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 11 publications
0
48
0
1
Order By: Relevance
“…4 For art restorers, another study has shown that it is possible to recognize an unknown pigment, in a pictorial layer, by comparison of its spectrum with a database made of elementary pigment spectra. 7 Because the spectrum shape is not affected by the translation due to a surface state change, this recognition remains possible, even if the surface of the painting is not planar.…”
Section: Discussionmentioning
confidence: 99%
“…4 For art restorers, another study has shown that it is possible to recognize an unknown pigment, in a pictorial layer, by comparison of its spectrum with a database made of elementary pigment spectra. 7 Because the spectrum shape is not affected by the translation due to a surface state change, this recognition remains possible, even if the surface of the painting is not planar.…”
Section: Discussionmentioning
confidence: 99%
“…A convenient technique for the nondestructive investigation of colored materials is the use of visible reflectance spectroscopy (Leona and Winter 2001;Dupuis et al 2002;Bacci et al 2009). In our study, we investigated dyes using the color spectrometer SPM 100 (Gretag-Imaging AG, Regensdorf, Switzerland), which measures the reflection of visible light (from 380 to 730 nm, spectral resolution 10 nm).…”
Section: Vis Reflectance Spectroscopymentioning
confidence: 99%
“…Finally, pigment identification under a varnish layer using diffuse reflectance spectrometry has already been performed on works of art thanks to the following homothetic approximation. 12 …”
Section: Linear Approximation Interestmentioning
confidence: 99%